Ask a New Question
Search
solve by useing elimination. 6x + 5y = 3 2x
solve by useing elimination.
6x + 5y = 3 2x + 3y = 13
1 answer
asked by
red
43 views
–x + 6y = –1 2x + 4y = 18 solve the equation by useing elimination
1 answer
asked by
red
44 views
4x + 10y = –4 –3x − 10y = 13solve by useing elimination
1 answer
asked by
red
50 views
Useing substitution/elimination method what is the solution set to x^2+y^2=25
4x-3y=0 a)(3,4) and (-3,-4) b)(3,-4) and (-3,4)
0 answers
asked by
Anonymous
648 views
x=-y+3
5x-y=-2 Solve using Elimination I already solved the equation using Substitution, Graphing, and a table I just need a
2 answers
asked by
M
732 views
Useing substitution/elimination method what is the solution set to 2x+y=1
x^2=y+2 a)(-3,7) and (1,-1) b)(3,7) and (-1,-1)
0 answers
asked by
Anonymous
682 views
solve by useing elimination7x − 8y = –3 7x − 4y = –19
1 answer
asked by
red
49 views
solve useing the addaditon and multiplication
6-6x > 3-5x x>?
1 answer
asked by
jessica
340 views
Please solve the system with the elimination method. Explain each step as it is performed.
5y = x 2x - 3y = 7 Would the
1 answer
asked by
cathy
1,184 views
use inver tangent ratio to solve this useing angles 20 and 25 what is vertex b
1 answer
21 views